2003
DOI: 10.1002/chir.10222
|View full text |Cite
|
Sign up to set email alerts
|

Configurational stability of chiral lithiated cyclopropylnitriles: A density functional study

Abstract: Chiral, configurationally stable lithiated nitriles would be valuable intermediates for asymmetric carbon-carbon bond-forming reactions. To gain insight into the design of such species, Walborsky's attempted enantioselective deprotonation/trapping reactions of a chiral cyclopropylnitrile were studied computationally up to the MP2(fc)/6-31+G* and B3LYP/6-31+G* levels. Investigation of cyclopropylnitrile/LiNH(2) deprotonation transition structures demonstrated a significant (20-23 kcal/mol) kinetic preference fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Carlier reported that the calculated inversion barrier for lithioacetonitirile is 0.45 kcal/mol, [15,16] and X-ray analysis of lithiophenylacetonitrile indicated that the geometry is planar. [17] The formation of enantiomer- ically enriched products by change in the O-substituent of the cyanohydrin from TBS to carbamoyl seems to be consistent with a pathway that involves an α-nitrile carbanion.…”
Section: Resultsmentioning
confidence: 99%
“…Carlier reported that the calculated inversion barrier for lithioacetonitirile is 0.45 kcal/mol, [15,16] and X-ray analysis of lithiophenylacetonitrile indicated that the geometry is planar. [17] The formation of enantiomer- ically enriched products by change in the O-substituent of the cyanohydrin from TBS to carbamoyl seems to be consistent with a pathway that involves an α-nitrile carbanion.…”
Section: Resultsmentioning
confidence: 99%
“…17 Under kinetic conditions the deuteration of chiral cyclopropanecarbonitrile 8 proceeds with greater than 99.9% stereochemical retention, implying the intermediacy of the pyramidal anion 9 18. Subsequent quests to generate chiral nitrile anions19 have proved challenging because of the relatively low barrier for inversion of the pyramidal nitrile anion 20…”
Section: 1 Introductionmentioning
confidence: 99%
“…Note that the depicted pyramidalization of the cyclopropyl anion in 6 is supported by calculations of the free anion;25 reduced angle strain is no doubt responsible for this preference 26. In addition we would like to point out that a “conducted tour” pathway25 to directly generate an ion‐pair like 7 would also be consistent with observed Δ S ≠ value and cannot be ruled out. Carbanion inversion of 7 and N → C migration would ultimately lead to enantiomerization of 2 .…”
Section: Methodsmentioning
confidence: 66%